SEKOLAH IDEAL PEKERJA ANAK: Ekspektasi dan Model Sekolah bagi Pekerja Anak di Pekalongan - Siti Mumun Muniroh (JURNAL PENELITIAN, 2013)
There are three focus issues in this research, which reveal expectations of child labor on education; ideal school model in their view and the type of knowledge and skills required by them. Observation and in-depth interview were used to obtain data to answer the issues. This research took place in Pekalongan City. The collected data were analyzed by using the interactive model. The results of this study revealed that the majority of child labor still had hopes for an increase in knowledge and skills, while some others felt that the current conditions had been enough for them and they did not have any expectations about school and skills enhancement. It also revealed that the ideal school model in their imagination was that the time and place of learning was flexible, fun friends and teachers, many practical matter, the cost was affordable and it could be used as a vehicle for the development of their talent and creativity. While the knowledge and skills required by them were to sustain their daily needs, such as trading, operating computers, drawing cartoons, salon or beauty, cooking and automotive.